Persepsi Akseptor Suntik Depomedroksi Progesteron Asetat di Puskesmas Giwangan Yogyakarta Perceptions of Acceptors of Depomedroxy Progesterone Acetate Injactable - Reni Merta Kusuma (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Background: KB’s acceptors are more interested to injection contraception. These are indicated by BKKBN statistic from several cities, including the ones in Lampung, West Kalimantan, and Central Java. It is interesting to examine the data in order to know perception of the acceptors of DMPA injection, especially regarding possible side effects caused by the usage of the contraception.Objective: To know perception of the acceptors of DMPA injection during their usage of the contraception.Method: Sampling technique used is accidental sampling. Informants are acceptors of DMPA injection receiving re-injection when data collection is being done. Informants are asked to attend to Directed Group Discussion (Diskusi Kelompok Terarah/DKT). The result of the discussion is transcribed and analyzed. The analysis is done by grouping the data.Result: Many informants have already used the DMPA injection for more than one year. Although it is a relatively long term usage, all of the informants do not know the way the contraception works. Not all informants feel the contraception’s side effects.Conclusion: Perceptions of the acceptors of DMPA injection about the contraception are generally positive. They can accept the DMPA injection. They can also accept the side effects as long as the uncomfortableness is still tolerable.Keywords: perception, acceptor, DMPA injection